ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA FINANCIAL STATEMENT FRAUD: PERSPEKTIF DIAMOND FRAUD THEORY (Studi Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2016) - Nugraheni, Nella Kartika; Triatmoko, Hanung (JURNAL AKUNTANSI DAN AUDITING, 2017)
This study aimed to analyze the factors that encourage financial statement fraud with analysis of diamond fraud theory. This research analyzes the influence of variable pressure proxied by financial targets, financial stability, external pressure, personal financial need, the opportunity proxied by nature of industry, ineffective monitoring, razionalization proxied by audit opinion, and the capability to replace any directors proxies against financial statements fraud. The sample in this research are 105 samples of banking companies listed on Indonesia Stock Exchange in the period 2014-2016. The results showed that the variable of financial targets as measured by return on asset, external pressure as measured by the leverage ratio, personal financial need as measured by the ownership of shares by the board of commission influence the financial statements fraud. The study did not found financial stability pressures as measured by the ratio of change total asset, ineffective monitoring as measured by the ratio of affiliated commissioner, nature of industry as measured by the ratio of change receivables, the audit opinion as measured by obtaining unqualified opinion with explanatory language, and capability as measured by changes of directors influence on fraudulent financial statements.